2004
DOI: 10.1079/bjn20031015
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and its relationship to cancer: an update

Abstract: Selenomethionine (Semet) is the major seleno-compound in cereal grains and enriched yeast whereas Se-methylselenocysteine (SeMCYS) is the major seleno-compound in Se-accumulator plants and some plants of economic importance such as garlic and broccoli exposed to excess Se. Animals can metabolize both Semet and SeMCYS. Epidemiological studies have indicated an inverse relationship between Se intake and the incidence of certain cancers. Blood or plasma levels of Se are usually lower in patients with cancer than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
424
0
21

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(449 citation statements)
references
References 135 publications
4
424
0
21
Order By: Relevance
“…Selenium (Se) is a dietary micronutrient that is essential for human health [23,29]. Cancer mortality is inversely correlated with estimated Se intake [8,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium (Se) is a dietary micronutrient that is essential for human health [23,29]. Cancer mortality is inversely correlated with estimated Se intake [8,29].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer mortality is inversely correlated with estimated Se intake [8,29]. Low Se intake or low plasma Se concentrations are associated with increased risk of colorectal cancer (CRC) [7,25] whereas in contrast, higher Se status is associated with lower risk of a recurrence of colonic tumours [15].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the selenium (Se) concentration of the microorganisms revealed that the ruminal microbial Se abundance was enriched relative to the level of Se in the diets. This concentration of Se in the ruminal microorganisms was significantly higher than that of the diet (Lyons and Jacques, 2001;Whanger, 2004). Ruminal bacteria are also able to synthesize Se-methionine (Se-Met) and Se-cysteine (Se-Cys), and these Se-amino acids (Se-AA) are then incorporated into the microbial protein.…”
mentioning
confidence: 99%
“…Ruminal bacteria are also able to synthesize Se-methionine (Se-Met) and Se-cysteine (Se-Cys), and these Se-amino acids (Se-AA) are then incorporated into the microbial protein. The predominant Se-AA was Se-Cys, when the ruminal microbes were incubated with Se IV or Se VI (Whanger, 2004). Microorganisms can reduce excessive doses of Se-compounds to unabsorbable elemental Se or selenide forms.…”
mentioning
confidence: 99%
“…In addition to nutritional needs for Se, the element also has health efficacy. It is also effective in reducing the incidence of some debilitating disorders (McKenzie et al 2001, Foresta et al 2002, Beck et al 2003, Soriano-Garcia 2004 and there is some evidence that Se plays a role as a cancer preventive agent when given in certain amounts (Ip 1998, Combs and Gray 1998, Fleming et al 2001, Whanger 2004.…”
Section: Introductionmentioning
confidence: 99%